Body Protein Sparing in Hibernators: A Source for Biomedical Innovation - Bertile, Fabrice; Habold, Caroline; Le Maho, Yvon; Giroud, Sylvain (Frontiers in Physiology, 2021)
Proteins are not only the major structural components of living cells but also ensure essential physiological functions within the organism. Any change in protein abundance and/or structure is at risk for the proper body functioning and/or survival of organisms. Death following starvation is attributed to a loss of about half of total body proteins, and body protein loss induced by muscle disuse is responsible for major metabolic disorders in immobilized patients, and sedentary or elderly people. Basic knowledge of the molecular and cellular mechanisms that control proteostasis is continuously growing. Yet, finding and developing efficient treatments to limit body/muscle protein loss in humans remains a medical challenge, physical exercise and nutritional programs managing to only partially compensate for it. This is notably a major challenge for the treatment of obesity, where therapies should promote fat loss while preserving body proteins. In this context, hibernating species preserve their lean body mass, including muscles, despite total physical inactivity and low energy consumption during torpor, a state of drastic reduction in metabolic rate associated with a more or less pronounced hypothermia. The present review introduces metabolic, physiological, and behavioral adaptations, e.g. energetics, body temperature, and nutrition, of the torpor or hibernation phenotype from small to large mammals. Hibernating strategies could be linked to allometry aspects, the need for periodic rewarming from torpor, and/or the ability of animals to fast for more or less time, thus determining the capacity of individuals to save proteins. Both fat- and food-storing hibernators rely mostly on their body fat reserves during the torpid state, while minimizing body protein utilization. A number of them may also replenish lost proteins during arousals by consuming food. The review takes stock of the physiological, molecular and cellular mechanisms that promote body protein and muscle sparing during the inactive state of hibernation. Finally, the review outlines how the detailed understanding of these mechanisms at play in various hibernators is expected to provide innovative solutions to fight human muscle atrophy, to better help the management of obese patients, or to improve the ex-vivo preservation of organs.